Peri-urban land use pattern and its relation to land use planning in Ghana, West Africa - Kleemann, Janina; Inkoom, Justice Nana; Thiel, Michael; Shankar, Sangeetha; Lautenbach, Sven; Fürst, Christine (Landscape and urban planning, 2017)
Population growth, Urban development, Urban sprawl, Land tenure, Land use change, Drivers, Confidence level analysis, Remote sensing, Interviews